The pre-oxidation kinetics and mechanism of sulfapyridine for biodegradability improvement - Pengcheng Yao; Lyujun Chen; Yongming Zhang; Wen, Donghui (Journal of Cleaner Production, 2021)
Oxidation of sulfapyridine (SPY) by typical oxidant, hydrogen peroxide (H2O2) and/or potassium peroxydisulfate (PDS), was used as a pre-treatment for antibiotic wastewater. The degradation dynamics showed that SPY was successfully removed, and the trend was fitted to the first-order reaction kinetics. H2O2 removed SPY more efficiently in acid condition than in basic condition, while PDS was the opposite. Better performance was achieved by using PDS than using H2O2, but combined using of PDS and H2O2 got the best performance. Although SPY was oxidized by those oxidants and biodegradability was improved, the intermediates still exhibited antibacterial activity. The degradation pathways and mechanism of SPY were deduced through density functional theory (DFT) and evidenced by intermediates product detection. Nucleophilic attack and radical attack were determined to be the major attack pathways in H2O2 and PDS systems, respectively. The SPY degradation pathways proposed in the two systems were based on the cleavage of bonds and hydroxyl substitution. Additionally, intermediate ΔG value showed that stubborn molecules remained in the wastewater even after pre-oxidation, which is harmful for further bio-treatment. This study provides a new insight for the improvement of biodegradability and the efficient degradation of SPY in antibiotic wastewater.